ADIBIS: A STORY OF OVERCOMING - Veloso, Mikaline Borges; da Rocha, Sandra Maria Amorim; Benevides, Siomary Cintia dos Santos (Seven Editora, 2025)
The article focuses on telling the life story of an Amazonian citizen who became an "Acre with a cracked foot" from his work as a hairdresser. His trajectory is worthy of sharing for migrants, young people and people who seek entrepreneurship in the far north as a way of survival, social ascension and leaving a legacy. The State of Acre has an economic and social history that has made it, today, a state with great challenges for the allocation of young people in the world of work. This reality is reflected in the story of Adibis who, with herculean effort, walked a successful path, considering the natural ability combined with learning, resilience and hard work, revolutionized his profession as a hairdresser in Acre. The act of sharing their history and protagonism is an instrument for raising awareness of new generations and Acre society. DOI: https://doi.org/10.56238/sevened2025.018-024